Back Cover: Molybdenum Speciation and its Impact on Catalytic Activity during Methane Dehydroaromatization in Zeolite ZSM‐5 as Revealed by Operando X‐Ray Methods (Angew. Chem. Int. Ed. 17/2016). Issue 17 (24th March 2016) - Lezcano‐González, Inés; Oord, Ramon; Rovezzi, Mauro; Glatzel, Pieter; Botchway, Stanley W.; Weckhuysen, Bert M.; Beale, Andrew M.
Abstract : The upgrading of methane into C2 –C6 hydrocarbons could prove a valuable alternative to oil as a source of platform chemicals. In their Communication onpage 5215 ff., A. M. Beale, B. M. Weckhuysen et al. describe how a combination of operando X‐ray methods and fluorescence lifetime imaging microscopy has been brought to bear on the well‐known Mo‐ZSM‐5 zeolite to provide a detailed understanding of how the Mo site evolves during the catalytic conversion of methane and how this influences the reaction products.